Students' Perception in Counceling and Guidance Towards Interest in Doing Counceling and Guidance - Nur Saqinah Galugu; Andi Ahmad Rifaldi; Saman (Psycho Holistic, 2021)
Interest is a mental activity that directs the tendency and attention to something so that it makes the individual interested in doing something. The biggest factor influencing interest is perception. This study aims to examine the relationship between perceptions of the counseling profession and students' interest in providing counseling services. The sample of this study was 59 students of the tenth grade at SMPN 1 Bua by using random sampling. The data was collected by using perseption scale towards counseling and guidence  and interest in doing counceling and guidence, and then the analyzed by using simple linear regression analysis. The results show that 41% students have positive perseption and 59% have negative perseption, while for the interest shows that 61% have low interest and only 39% have hight interest. Based on the correlation test shows sig value (2-tailed) 0.002<0.05. Thus, it can be concluded that both of the variables have positive correlation. The results of this study indicate that the students' perceptions of the guidance and counseling profession contribute to students' interest in doing counseling services at school.